Identification of differential plasma miRNA profiles in Chinese workers with occupational lead exposure. Issue 5 (31st October 2017) - Xu, Ming; Yu, Zhengmin; Hu, Feifei; Zhang, Hongbing; Zhong, Lixin; Han, Lei; An, Yan; Zhu, Baoli; Zhang, Hengdong
Abstract : Elevated lead absorptions are hazardous factors in lead-related workers. Previous studies have found its toxic impacts on nervous, circulatory, and metabolic systems. We hypothesized that alteration of miRNAs profile in plasma was closely associated with lead exposure. We analyzed to identify lead-related miRNAs in workers occupationally exposed to lead. Microarray assay was performed to detect plasma miRNA between workers with high and minimal lead exposure in the discovery stage. The following prediction of miRNAs' candidate target genes was carried out by using miRecords, STRING, and KEGG databases. We finally identified four miRNAs significantly associated with high level of blood lead. miR-520c-3p (* P =0.014), miR-211 (* P =0.019), and miR-148a (* P =0.031) were downexpressed in workers with high lead exposure and with high blood lead level (BLL), while miR-572 (* P =0.027) displayed an opposite profile. Functional analysis of miRNAs displayed that these miRNAs could trigger different cellular genes and pathways. People under chronic lead exposure had a diverse 'fingerprint' plasma miRNA profile. Our study suggested that miR-520c-3p, miR-211, miR-148a, and miR-572 were the potential biomarkers for lead susceptibility in Chinese.